Investigation of Copy Number Variations (CNVs) of the Goat PPP3CA Gene and Their Effect on Litter Size and Semen Quality - Yangyang Bai; Taiyuan Zhang; Nuan Liu; Congliang Wang; Zhengang Guo; Chuanying Pan; Haijing Zhu; Xianyong Lan (Animals, 2022)
Copy number variations (CNVs) have many forms of variation structure, and they play an important role in the research of variety diversity, biological evolution and disease correlation. Since CNVs have a greater impact on gene regulation and expression, more studies are being finalized on CNVs in important livestock and poultry species. The protein phosphatase 3 catalytic subunit alpha (PPP3CA) is a key candidate gene involved in the goat fecundity trait, and has important effects on precocious puberty, estrogen signal transduction pathways and oocyte meiosis. Additionally, PPP3CA also has a dephosphorylation effect in the process of spermatogonial stem cell meiosis and spermatogenesis. So far, there is no research on the relationship between the copy number variations of the PPP3CA gene and reproduction traits. Therefore, the purpose of this study was to determine the association between copy number variations in the goat PPP3CA gene and litter size and semen quality in Shaanbei white cashmere goats (SBWC) (n = 353) and Guizhou Heima goats (n = 64). Based on the association analysis, the results showed that only CNV1 and CNV2 within the PPP3CA gene were distinctly related to the first-birth litter size in female goats (p = 7.6802 × 10−11; p = 5.0895 × 10−9, respectively) and they were also significantly associated with the semen quality of SBWC goats (p < 0.05). In addition, individuals with Loss genotypes demonstrated better phenotypic performance compared to those with other types. Therefore, CNV1 and CNV2 of the PPP3CA gene are potentially useful for breeding, as they are linked to important goat reproduction traits.